Las WebQuest y el aprendizaje cooperativo. Utilización en la docencia universitaria - Gallego Gil, Domingo (Revista Complutense de Educación, 2007)
WebQuest is a didactic resource based on the constructivism learning and in the cooperative methodology. At the moment it is very successful in the Pre-school, Primary and Secondary level. Through this article we try to show an utilization proposal of this resource at the university level, destined on the one hand to future educators (Teaching and Pedagogy Qualifications) and, on the other hand, to teachers and students from different careers independently of its speciality or object of education. WebQuest is a simple and accessible strategy. It is accessible to teachers from different levels, without dominating in a technical way the information and communication technologies in order to introduce them in their education methodology as a didactic resource